Penerapan Keterampilan 4C (Critical Thinking, Creativity, Collaboration, Communication) Dalam Pembelajaran Abad 21 di Sekolah Dasar - Taufiqullah Dahlan; Wanti Nurasiah; Intan Lestari Nur Inayah; Fadillah Azkia; Aulia Dwi Ardhiana; Aida Zahwa; Atiya Nashwa Raushani (Journal of Innovative and Creativity, 2026)
The implementation of 4C skills (Critical Thinking, Creativity, Collaboration, and Communication) is the main keyto realizing 21st-century learning that is relevant to global demands. This study aims to describe the strategy forimplementing 4C in elementary schools and analyze its impact on student engagement and learning outcomes. Thestudy used a qualitative descriptive approach with exploratory study techniques on various literature andimplementation practices in elementary schools. The results of the study indicate that 4C skills can be developedeffectively through active learning models such as Project Based Learning (PjBL), Problem Based Learning (PBL),and Collaborative Learning. Teachers play a crucial role as facilitators, innovators, and motivators who createcontextual and meaningful learning experiences. A school environment that supports collaboration, creativity, andcommunication is an external factor determining success. The positive impact of 4C implementation is seen inimproving students' critical thinking skills, creativity, cooperation, and self-confidence. However, teachers still faceobstacles such as limited time, facilities, and pedagogical competence. Therefore, it is necessary to strengthen teachercapacity through training, support from school facilities, and collaboration with parents to create an adaptive andsustainable learning ecosystem. Overall, implementing the 4Cs is an essential strategy for developing a young generationthat is critically thinker, creative, communicative, and able to collaborate in facing the dynamics of the 21st century